Macrocyclic gelators - Goh, Ching; Mocerino, Mauro; Ogden, Mark (Taylor and Francis Ltd, 2013)
The field of low molecular weight supramolecular gels, also known as physical gels, has grown rapidly over the last decade. In these gels, small molecules (gelators) self-assemble through non-covalent interactions, usually into a network of fibres, to trap solvent. Many physical gels are responsive to stimuli and often these types of gels can be reversibly converted from gel to sol. These properties make them ideal candidates for investigation into a range of potential applications, including biomedical, smart materials, sensors and catalysts. This review provides an overview of macrocyclic compounds, particularly the calixarenes, that can form supramolecular gels.